2008
DOI: 10.1586/14760584.7.4.467
|View full text |Cite
|
Sign up to set email alerts
|

Age-related decline in immunity: implications for vaccine responsiveness

Abstract: Aging is associated with declines in immune system function, or 'immunosenescence', leading to progressive deterioration in both innate and adaptive immunity. These changes contribute to the decreased response to vaccines seen in many older adults, and morbidity and mortality from infection. Infections (e.g., influenza, pneumonia and septicemia) appear among the top ten most-common causes of death in adults in the USA aged 55 years and older. As immunosenescence has gathered more attention in the scientific an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
84
0
9

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(94 citation statements)
references
References 119 publications
1
84
0
9
Order By: Relevance
“…Moreover, the inability of old individuals to effectively respond to vaccines results in less effective immunizations against viruses and bacteria, thus increasing the risk of infections and diseases (Miller and Cancro 2007;Cancro et al 2009;Gibson et al 2009;Dunn-Walters and Ademokun 2010;Frasca and Blomberg 2011). Indeed, it is well documented that the immune response to vaccination declines with age, although the reasons for this are poorly understood (Kumar and Burns 2008;Frasca et al 2010;McElhaney et al 2012). It is also known that in the elderly, there is an impairment of both innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the inability of old individuals to effectively respond to vaccines results in less effective immunizations against viruses and bacteria, thus increasing the risk of infections and diseases (Miller and Cancro 2007;Cancro et al 2009;Gibson et al 2009;Dunn-Walters and Ademokun 2010;Frasca and Blomberg 2011). Indeed, it is well documented that the immune response to vaccination declines with age, although the reasons for this are poorly understood (Kumar and Burns 2008;Frasca et al 2010;McElhaney et al 2012). It is also known that in the elderly, there is an impairment of both innate and adaptive immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…It has been widely reported that elderly people show changes in B cell number, low levels of antibody production, and poor responses to recall antigens, and a collapse in B cell receptor repertoire diversity correlated with poor health status and the impairment of antibody response (Miller and Cancro 2007;Kumar and Burns 2008;Cancro et al 2009;Gibson et al 2009;DunnWalters and Ademokun 2010;Frasca et al 2010;Frasca and Blomberg 2011;McElhaney et al 2012). Lower numbers and percentages of B cells also form part of the cluster of immune parameters collectively known as the "Immune Risk Profile" associated with 2-, 4-, and 6-year mortality of the very elderly in the Swedish OCTO/ NONA longitudinal studies (Pawelec et al 2005).…”
Section: Cd24mentioning
confidence: 99%
“…The effectiveness of a vaccine, however, depends on the competency of the individual immune system to adequately respond to that vaccine (1,2). For example, patients vaccinated within 2 wk before starting immunosuppressive therapy or while receiving immunosuppressive therapy are considered unvaccinated and are, therefore, advised to be revaccinated at least 3 mo after therapy is discontinued if immune competence has been restored (1).…”
mentioning
confidence: 99%
“…For example, patients vaccinated within 2 wk before starting immunosuppressive therapy or while receiving immunosuppressive therapy are considered unvaccinated and are, therefore, advised to be revaccinated at least 3 mo after therapy is discontinued if immune competence has been restored (1). The deterioration in both innate and adaptive immunity associated with aging also leads to reduced responses to vaccines and increases morbidity and mortality from infection (2). Recently, the Centers for Disease Control and Prevention (CDC) identified smokers as a population with higher incidence and severity of infectious diseases and recommended vaccines for all smokers aged 19-64 y (3, 4).…”
mentioning
confidence: 99%
“…Nosocomial influenza transmission is complicated by the fact that HCWs shed the virus while asymptomatic and routinely report to work with symptomatic influenza illness [17]. An additional consideration is that influenza immunization of some vulnerable patient groups may result in suboptimal immune responses, making immunization of those in contact with them critical [18][19][20][21][22]. Median patient mortality rates during nosocomial influenza outbreaks have been reported to be 16% in acute care and geriatric facilities, and as high as 33-60% in transplant or intensive care units [23].…”
Section: "Seasonal Influenza Epidemicsmentioning
confidence: 99%